Taḥawwula At-Ta̒līmi Al-Lughati Al-̒Arabiyyati Fī Al-̒Aṣri Ar-Raqmiyyi: Taḥlīlu Al-Adabiyyāti An-Namāżiji Wa Al-Istīrātījiyyāti At-Ta̒līmi Al-Qāimi At-Tiknūlūjiya - Ika, Mazi Septina Mirantika (Pascasarjana Universitas Islam Negeri Mataram, 2025)
This research aims to analyze the transformation of Arabic language education in the digital era using library research with a qualitative approach. A review of contemporary literature dealing with educational models and educational strategies supported by technology, such as e-learning, mobile applications, and interactive learning platforms. The results of the study revealed that the integration of digital technology in Arabic language teaching contributes to enhancing interaction and learners motivation, providing a personalized and flexible learning opportunity that transcends the boundaries of time and space. However, this transformation requires teachers to have technical and pedagogical qualifications and the development of high-quality educational content aligned with learners characteristics and needs. The research recommends designing clear technology-based educational strategies. It also suggests adopting modern pedagogical models to ensure the effectiveness and sustainability of Arabic language education in light of the rapid digital changes.